An Investigation of Pulse Oximetry Levels During Swallowing in Healthy Adults and in Individuals with Severe and Very Severe Chronic Obstructive Pulmonary Disease - Alani, Salim S.; Stierwalt, Julie A.G.; LaPointe, Leonard L.; Morris, Richard J.; Jeong, Allan C.; Filson Moses, Jennifer; Upton, Thomas D. (Seminars in Speech and Language, 2022)
To compare pulse oximetry (PO) levels during swallowing in healthy adults and adults with severe chronic obstructive pulmonary disease (COPD). Participants included two groups of 60 healthy adults, balanced for gender. The young group ranged from 18 to 38 years, and the older group from 60 to 87 years. In addition, there were 11 participants with COPD aged 43 to 82 years. PO levels were collected as each participant swallowed 10 mL of water, 10 mL of applesauce, and a piece of diced pear (three trials each). Analyses for the healthy groups revealed neither statistically significant main effects for bolus type nor interactions between gender and age. For between-subject effects, there was no main effect for gender, but there was a large main effect for age, and a gender and age interaction. In the group with COPD, there were no significant differences across bolus types; however, PO measures were consistently lower than the healthy groups for all bolus types. Healthy adults exhibited stable PO levels across bolus types. Adults with COPD, although exhibiting significantly lower PO levels, also remained stable. For clinicians who monitor PO measures, these results offer a more comprehensive understanding of the nature of these measures during swallowing in these groups.
Keywords: pulse oximetry; dysphagia; swallowing; swallowing disorders; COPD